Defect‐Engineered Atomically Thin MoS2 Homogeneous Electronics for Logic Inverters. Issue 2 (19th November 2019) - Gao, Li; Liao, Qingliang; Zhang, Xiankun; Liu, Xiaozhi; Gu, Lin; Liu, Baishan; Du, Junli; Ou, Yang; Xiao, Jiankun; Kang, Zhuo; Zhang, Zheng; Zhang, Yue
Abstract: Ultrathin molybdenum disulfide (MoS2 ) presents ideal properties for building next‐generation atomically thin circuitry. However, it is difficult to construct logic units of MoS2 monolayer using traditional silicon‐based doping schemes, such as atomic substitution and ion implantation, as they cause lattice disruption and doping instability. An accurate and feasible electronic structure modulation strategy from defect engineering is proposed to construct homogeneous electronics for MoS2 monolayer logic inverters. By utilizing the energy‐matched electron induction of the solution process, numerous pure and lattice‐stable monosulfur vacancies (Vmonos ) are introduced to modulate the electronic structure of monolayer MoS2 via a shallow trapping effect. The resulting modulation effectively reduces the electronic concentration of MoS2 and improves the work function by 100 meV. Under modulation of Vmonos, an atomically thin homogenous monolayer MoS2 logic inverter with a voltage gain of 4 is successfully constructed. A brand‐new and practical design route of defect modulation for 2D‐based circuit development is provided. Abstract : Accurate and facile solution‐processable defect engineering is proposed for constructing atomic‐thin MoS2 homogeneous electronics. By utilizing the energy‐matched relationship between the formation energy of monosulfur vacancies (Vmonos ) and the electron induction energy of H2 O2 aqueous solution, numerous pure and lattice‐stable Vmonos are introduced for modulating electronic structure to construct homogeneous electronics including a logic inverter via the shallow trapping effect.